Pengaruh Work Family Conflict dan Stres Kerja terhadap Komitmen Pegawai di Biro SDM Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi Republik Indonesia - Suryana, Nana Ade; Utama, Zahera Mega; Fajarusman, Bambang (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This research is about the phenomenon of employees who work in government institutions and also play a role in the household and family. These two different roles are considered to have an impact on work activities which cause stress in the implementation of work which in turn also affects the implementation of employee work commitments. The aim of the research is to determine the influence of work family conflict and work stress on employee work commitment at the HR Bureau of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. The research method uses a quantitative approach with survey methods. Data analysis using the classic assumption test and t test. The research results explain that there is a significant influence between work family conflict and work stress and employee commitment, but the relationship is negative. The simultaneous test between work-family conflict and work stress and employee commitment also explains a significant relationship.